Hitra ocena potreb in storitev za načrtovanje dezinstitucionalizacije - Rafaelič, Andreja (Socialno delo, 2016)
The aim of the article is to systematically and chronologically analyse research that has been done in social work on deinstitutionalisation and that contributed to the development of the rapid assessment and response method (RAR). The heritage of action research in social work that contributed to the development of the RAR in Slovenia, is summarised. The development of action research and RAR in Slovenia has been divided into four phases: (1) the beginnings of action research with the socio-therapeutic projects, (2) the development of the methodology of action research, (3) implementation of social care system and (4) the development of long-term care and activism research. The RAR, as it was developed in Slovenia, is at the moment a very important tool because it enables research and also deinstitutionalisation planning. Slovenia is set to introduce the systematic implementation of deinstitutionalisation therefore it is especially important to have a good and systematic research plan, but also to be able to do it quickly and with focus on development.
Keywords: deinstitutionalisation; socialno skrbstvo; hitra ocena potreb; action research; activism research; dezinstitucionalizacija; akcijsko raziskovanje; social care; aktivistično raziskovanje; raziskave